2013
DOI: 10.1017/s1431927613005618
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Orientation Measurements using EBSD

Abstract: Routine EBSD analysis typically applies a 2D Hough transform technique. This requires collection and background correction of the Kikuchi pattern. A Hough transform is applied to highlight and locate the Kikuchi bands. These bands are revealed as local peaks in the resulting Hough space and their corresponding maxima are found automatically, locating the position and direction of the Kikuchi bands and the corresponding diffraction planes. In this primary band detection routine each maximum is represented by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 3 publications
2
22
0
1
Order By: Relevance
“…Transmission samples were produced by first dimple grinding electro-discharge 5 machined 3 mm diameter discs with a 1 μm diamond suspension to just 20 μm thick (Dimple Grinder 656, Gatan, USA) and then thinning until perforation in a twinjet electropolisher (Tenupol-5, Struers, Denmark) using a solution of 5% perchloric acid, 35% butanol, 60% methanol by volume held at 32 V and -30 °C. TKD was carried out on a dual beam FIB/SEM (Helios NanoLab, FEI, USA) with an EBSD detector and acquisition software (NordlysNano, Oxford Instruments, UK) employing the refined accuracy routine [20] at 30 kV, 6.4 nA, -20 ° tilt, a working distance of 1.5 mm and a 20 nm stepsize.…”
Section: Materials and Metallographic Preparationmentioning
confidence: 99%
“…Transmission samples were produced by first dimple grinding electro-discharge 5 machined 3 mm diameter discs with a 1 μm diamond suspension to just 20 μm thick (Dimple Grinder 656, Gatan, USA) and then thinning until perforation in a twinjet electropolisher (Tenupol-5, Struers, Denmark) using a solution of 5% perchloric acid, 35% butanol, 60% methanol by volume held at 32 V and -30 °C. TKD was carried out on a dual beam FIB/SEM (Helios NanoLab, FEI, USA) with an EBSD detector and acquisition software (NordlysNano, Oxford Instruments, UK) employing the refined accuracy routine [20] at 30 kV, 6.4 nA, -20 ° tilt, a working distance of 1.5 mm and a 20 nm stepsize.…”
Section: Materials and Metallographic Preparationmentioning
confidence: 99%
“…EBSD data were acquired in 'refined accuracy' mode. [16] This mode improves the angular resolution. Experiments confirmed that low misorientation angles as small as 0.2 deg were reliably detected.…”
mentioning
confidence: 98%
“…Since EBSD is an orientation measurement technique, improving the angular resolution of the technique is of most interest to researchers. Methods to improve angular resolution have been developed such as the pattern comparison method [2], iterative indexing [3], the 3D-Hough transform [4] and HR-EBSD [5]. In particular, the high resolution (or high angular resolution) electron backscatter diffraction (EBSD) technique is capable of characterizing additional information such as residual stress/strain [6].…”
Section: Introductionmentioning
confidence: 99%